Study of charge carrier transport properties and lifetimes in HR GaAs:Cr with Timepix3. (20th December 2021) - Smolyanskiy, P.; Bergmann, B.; Billoud, T.; Burian, P.; Sitarz, M.; Søndergaard, C.; Pospíšil, S.
Abstract: The response of a Timepix3 (256 × 256 pixels, pixel pitch 55 μm) detector with a 500 μm thick HR GaAs:Cr sensor was studied in proton beams of 125 MeV at the Danish Centre for Particle Therapy in Aarhus, Denmark and in a 120 GeV/ c pion beam at the Super-Proton Synchrotron (SPS) at CERN. The sensor was biased at different voltages and irradiated at different angles. The readout chip was configured to operate in electron and hole collection modes. Measurements at grazing angles allowed to see elongated tracks with well-defined impact and exit points, so that charge carrier production depths could be determined in each pixel. We extracted the charge collection efficiencies and the charge carrier drift times as a function of the distance to the pixel plane. It was found that measured proton tracks are shorter in hole collection than in the case of electron collection, which is explained by the shorter lifetime of holes. At an angle of 60 degrees with respect to the sensor normal, the average track length in hole collection was ∼700 μm and 950 μm in electron collection mode. To understand the experimental findings, models describing the properties of HR GaAs:Cr were implemented into the Allpix 2 simulation framework. We added previously presented experimental results describing the dependence of the electron drift velocity on the electric field and validated the response by comparing measurement and simulation for various X- and gamma-ray sources in the energy range of 10–60 keV. By comparison of the experimental and the simulated results, the mobility μ h and the lifetime of holes τ h were estimated as μ h = (320 ± 10) cm 2 /V/s and τ h = (4.5 ± 0.5) ns.